PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS I SDN 006 TRI MULYA JAYA - Tukirah Kurniasih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low science (IPA) learning outcomes of students, where out of 20 students only 9 students achieved learning mastery and the average student learning outcome was 62, which was still below the minimum mastery criterion (KKM) of 65. This research aimed to improve the science learning outcomes of first-grade students at SDN 006 Tri Mulya Jaya. The study was conducted as a classroom action research carried out in two cycles by applying a direct instructional model. The data used in this research consisted of teacher activity data, student activity data, and students’ science learning outcomes. The results indicated that the application of the direct instructional model had a positive impact by increasing teacher and student activities as well as students’ science learning outcomes. Teacher activity increased from 37.00% in the first meeting of cycle I to 50.00% in the second meeting of cycle I, then to 74.00% in the first meeting of cycle II, and finally to 82.00% in the second meeting of cycle II. Student activity also increased from 37.00% in the first meeting of cycle I to 41.00% in the second meeting of cycle I, then to 76.00% in the first meeting of cycle II, and to 80.00% in the second meeting of cycle II. Students’ science learning outcomes also improved, as indicated by the increase in the number of students achieving mastery from 14 students (70.00%) in the first cycle to 17 students (85.00%) in the second cycle. Likewise, the class average score increased from 62 in the preliminary data to 72.5 after the first cycle and further increased to 76.5 after the second cycle.